(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
The structure-forming properties of mineral conditioners caused by acidic treatment have been studied by means of turbidimetry as well as particles size distribution methods. Three types of mineral conditioner having СаО, SO42– and РO43– groups on the surface have been investigated. The first two types were treated with nitric acid, and the third with phosphoric acid. The treatment of mineral conditioners with phosphoric acid causes a decrease in the effluent turbidity, whereas when treating СаО group containing mineral conditioner with nitric acid a sharp increase in this parameter is observed. When treating sulfo group mineral conditioner this increase is not significant.